An open book on Facebook? Examining the interdependence of adolescents' privacy regulation strategies. Issue 9 (1st September 2016) - Heirman, Wannes; Walrave, Michel; Vermeulen, Anne; Ponnet, Koen; Vandebosch, Heidi; Van Ouytsel, Joris; Van Gool, Ellen
ABSTRACT: Users of social network sites (SNSs) use three main strategies that help to manage the privacy of their profile information: (1) limiting the level of data revealed, (2) using privacy settings to exert control over data and (3) audience/friendship management by being restrictive about whom to accept as a 'friend'. Extant research does not show whether these strategies operate as independent mechanisms or whether they are interdependent and work as a system . Given what offline privacy theorist Irwin Altman (1977 ) designates as the multi-mechanic nature of privacy protection, we test a model in which we expect to find that the three discerned strategies are related to one another. Structural equation modelling analysis performed on the subsample ( n  = 1564) of our study's data – collected among 1743 adolescents by means of a paper-and-pencil survey – demonstrates that, in line with Altman's vision of privacy protection, the three discerned strategies effectively operate as an interdependent system. In congruence with the hypotheses derived from extant research, we found that adolescents' level of disclosure influences adolescents' involvement in the two other discerned strategies: Adolescents with high levels of personal information disclosure share an increased tendency to have many friends on SNSs and a lower level of using privacy settings.